WATER AND AIR POLICE CORPS (POLAIRUD) AUTHORITY IN PREVENTING THEFT ON LEGO ANCHORS SHIPS IN THE TANJUNG PRIOK PORT AREA - Surya Wahyudi; Tofik Yanuar Candra; Mohamad Ismed (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
The aim of the research is to analyze the authority of Water and Air Police Corps (Korpolairud) in preventing the crime of theft on ships with Lego anchors in the Tanjung Priok port area as well as analyzing the legal protection of ships anchored in the Tanjung Priok port area. The type of research used is normative juridical. The approaches used in legal research are the statute approach, the case approach and the comparative approach. The results of the analysis show that Polairud's Authority in preventing criminal acts of theft, Article 1 paragraph (1) of the 1945 Constitution of the Republic of Indonesia is a state based on law. The rule of law is a constitutional construction. As such, all actions of law enforcement officials including the police in carrying out investigations must be based on the law and obey the law. Legal protection for Lego Anchor Ships in the Tanjung Priok Port Area, it can be understood that police institutions, especially the Sub-Directorate of Gakkum Ditpolair Korpolairud Baharkam Polri as an organization carry out administrative and management functions in carrying out their functions or duties as investigators of criminal acts of theft onboard Lego Anchors in the Region Tanjung Priok Port which has been determined by laws and regulations.